O direito de voto e o voto múltiplo nas sociedades anônimas - Cárgano, Márcia Spinel de Souza (2007)
This study aims to understand not only how the multiple vote works and its mathematics, instituted by the article 141 of Brazilian Corporations Act (Lei das S.A.), but also the practicing of the right to vote. The Brazilian Corporations Act has implemented the multiple vote with the idea of multiplying the number of stocks by the number of members who will be elected. This criterion was originally adopted for the parliamentarians election in England and in the United States. The minor stockholders, apart from the other minor stockholders or together with them, will always be minor. According to the existing established conditions, they will never get the board of director s control, but, at least, they get the controller s attention to their existence when they carry out their right to vote and, mainly, their right of being able to elect. The Multiple Vote, which is found in Brazilian Corporations Act Law n. 6.404, dated December, 15 1976 , mainly considering the percentage reduction of detained stocks given by Brazilian Securities Commission (Comissão de Valores Mobiliários CVM), brings to the minor stockholders the possibility of participating in the corporation management in which they maintain their invested equity. The Corporative Management concept influences more and more the stock market and the stock corporations laws, allowing to the investors the possibility of participating in the decisions with the control block and the chance of accessing the company information